An Analysis of the Effect of Economic Growth, Education, and Health on Poverty in East Java - Qudsi, Hanif; Ashar, Khusnul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze the impact of economic growth, education, and health on poverty in East Java Province during the 2018-2023 period. This study is motivated by the high poverty rate in East Java compared to other provinces in Indonesia, despite having a smaller population. The Human Capital Theory and Amartya Sen's Poverty Theory are used as theoretical foundations. The data used is secondary data from Badan Pusat Statistik (BPS), covering 38 districts/cities in East Java Province. The analytical method used is multiple linear regression with panel data. The results of the study show that economic growth, education, and health have a significant negative effect on the poverty rate. Economic growth measured through GDP, the average length of schooling as an education indicator, and life expectancy as a health indicator, all contribute to the reduction of poverty. These findings indicate the importance of improvements in the economic, education, and health sectors to reduce poverty in East Java. The implications of this study can help the government and other stakeholders formulate effective policies for poverty alleviation in the region. Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh pertumbuhan ekonomi, pendidikan, dan kesehatan terhadap kemiskinan di Provinsi Jawa Timur selama periode 2018-2023. Penelitian ini dilatarbelakangi oleh tingginya tingkat kemiskinan di Jawa Timur dibandingkan provinsi lain di Indonesia, meskipun dengan jumlah penduduk yang lebih sedikit. Teori Human Capital dan Teori Kemiskinan Amartya Sen digunakan sebagai landasan teoretis. Data yang digunakan merupakan data sekunder dari Badan Pusat Statistik (BPS), mencakup 38 kabupaten/kota di Provinsi Jawa Timur. Metode analisis yang digunakan adalah regresi linier berganda dengan data panel. Hasil penelitian menunjukkan bahwa pertumbuhan ekonomi, pendidikan, dan kesehatan berpengaruh negatif signifikan terhadap tingkat kemiskinan. Pertumbuhan ekonomi yang diukur melalui PDRB, rata-rata lama sekolah sebagai indikator pendidikan, dan angka harapan hidup sebagai indikator kesehatan, semuanya berkontribusi terhadap penurunan kemiskinan. Temuan ini mengindikasikan pentingnya peningkatan dalam sektor ekonomi, pendidikan, dan kesehatan untuk mengurangi kemiskinan di Jawa Timur. Implikasi penelitian ini dapat membantu pemerintah dan pemangku kepentingan lainnya dalam merumuskan kebijakan yang efektif untuk pengentasan kemiskinan di daerah tersebut.